Okra Mucilage Extract as A Co-Surfactant Increased the Curcumin Nanoemulsion Stability and Encapsulation Efficiency - El Fajriyah Aulia Putri; Ellya Indahyanti; Diah Mardiana; Maria Lucia A.D Lestari; Zubaidah Ningsih (Science and Technology Indonesia, 2023)
Curcumin has various bio-functional properties; however, curcumin poor bioavailability reduces its efficacy. Nanoemulsion delivery system is an alternative method improving curcumin bioavailability in which surfactant and oil used, play an important role in determining nanoemulsion properties. Several studies on curcumin nanoemulsions apply synthetic surfactants which can be harmful if they are added excessively. This study aims to use a natural emulsifying agent, namely okra mucilage extract (OME), and determine its effectiveness as co surfactant. OME is safe to use as an emulsifying agent because it is natural, harmless, safe, biodegradable and eco-friendly. Liquid-liquid and microwave extraction methods were used to obtain OME which was further identified using Fourier Transfer Infrared Spectroscopy (FTIR). Meanwhile, sonication method was used to produce curcumin nano-emulsion (CurN). The particle size and polydispersity index of curcumin nano-emulsion were measured using Particle Size Analyzer (PSA) with Dynamic Light Scattering (DLS) technique, while the morphology of the nanoemulsion was observed using a Digital Imaging Microscope and Confocal Laser Scanning Microscope (CLSM). The results showed that the addition of 0.0160 g OME at a ratio of 1:5 (OME: Tween 80) in the preparation of 5 mL of CurN was able to reduce the particle size and polydispersity index from 740.80 ± 9.70 nm to 289.20 ± 2.23 and 0.340 ± 0.005 to 0.165 ± 0.008 respectively. OME increased the encapsulation efficiency from 77.93 ± 6.59% to 87.17 ± 1.12% which was confirmed by the augmentation of the fluorescence intensity of curcumin from 192.82 to 388.55. The addition of OME also maintained the stability of the CurN up to 14 days of storage at 4°C.